Quercetin potentiates insulin secretion and protects INS-1 pancreatic β-cells against oxidative damage via the ERK1/2 pathway - Youl, E (Blackwell Publishing Ltd, 2010)
BACKGROUND AND PURPOSE: Quercetin lowers plasma glucose, normalizes glucose tolerance tests and preserves pancreatic β-cell integrity in diabetic rats. However, its mechanism of action has never been explored in insulin-secreting β-cells. Using the INS-1 β-cell line, the effects of quercetin were determined on glucose- or glibenclamide-induced insulin secretion and on β-cell dysfunctions induced by hydrogen peroxide (H(2)O(2)). These effects were analysed along with the activation of the extracellular signal-regulated kinase (ERK)1/2 pathway. N-acetyl-L-cysteine (NAC) and resveratrol, two antioxidants also known to exhibit some anti-diabetic properties, were used for comparison. EXPERIMENTAL APPROACH: Insulin release was quantified by the homogeneous time resolved fluorescence method and ERK1/2 activation tested by Western blot experiments. Cell viability was estimated by the [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide] (MTT) colorimetric assay. KEY RESULTS: Quercetin (20 µmol·L(−1)) potentiated both glucose (8.3 mmol·L(−1))- and glibenclamide (0.01 µmol·L(−1))-induced insulin secretion and ERK1/2 phosphorylation. The ERK1/2 (but not the protein kinase A) signalling pathway played a crucial role in the potentiation of glucose-induced insulin secretion by quercetin. In addition, quercetin (20 µmol·L(−1)), protected β-cell function and viability against oxidative damage induced by 50 µmol·L(−1) H(2)O(2) and induced a major phosphorylation of ERK1/2. In the same conditions, resveratrol or NAC were ineffective. CONCLUSION AND IMPLICATIONS: Quercetin potentiated glucose and glibenclamide-induced insulin secretion and protected β-cells against oxidative damage. Our study suggested that ERK1/2 played a major role in those effects. The potential of quercetin in preventing β-cell dysfunction associated with diabetes deserves further investigation.